PENGARUH PEMUPUKAN NPK TERHADAP HASIL BAWANG MERAH DI LAHAN PASIR PANTAI (THE EFFECT OF NPK FERTILIZER ON SHALLOT YIELD AT COASTAL SANDY LAND) - Rajiman, Rajiman (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2009)
This research was aimed to study the effect of NPK fertilizer to shallots yield at Bugel area' the research was conducted with completely randomized design consisting two factors. The first factor was nitrogen (N) proportions: l/3, 2/3 and dosages. The second factor was phosphor*potassium proportions: I/3, 2/3 and t dosages. The fertilizer recommendation were 250 kg.ha-1 Urea, 150 kg.ha-1 ZA, TSP and KCL. For comparison purposes; the control plot did not use any fertilizer. The parameters of observation were bulb total, the fresh and dry weight, harvest index and bulb diameter. The data were analyzed by variances and orthogonal contrast 5%. The results showed that there was no significant interaction between nitrogen and phosphor + potassium, level, except bulb total and harvest index. The application of nitrogen and phosphor + potassium was not significant on the yield of fresh bulb, dry bulb and bulb diameter.